Visualizing Tourism Sustainability through Smart Tourism Technology in Lake Toba, Indonesia - Robert La Are; Tonny Hendratono; John JOI Ihalau; Asep Syaiful Bahri; Ema Rahmawati (CV. Syntax Corporation Indonesia, 2025)
Lake Toba, is one of the tourist destinations currently being developed into a leading destination in the North of Sumatera, Indonesia. With the cultural diversity of the Batak Tribe and its rich history, Lake Toba has become a popular destination for both domestic and international tourists. One of the key concepts implemented in this destination is the application of digital technology, such as online payment, online information, and online booking and reservation systems. This study analyses the impact of technology utilization on the well-being of tourists visiting Lake Toba. Focusing on smart tourism technology, this research explores the relationship between digital usage experience, memorable tourism experiences, revisit, and tourist recommendations. Data were collected through surveys of tourists who had visited Lake Toba. A quantitative analysis method was used to examine the relationships between variables. The results show that using smart tourism technology significantly enhances the tourist experience, positively affecting their intention to revisit and recommend the destination to others. Memorable tourism experiences also play a key role in improving the overall well-being of tourists. This research contributes to developing technology-based tourism strategies to enhance tourist satisfaction which will lead to revisit and recommendations, ultimately influencing tourist behavior.